Plant biomass as organic fuel - Осьмак, Алексей Алексеевич; Серегин, Александр Александрович (Eastern-European Journal of Enterprise Technologies, 2014)
Application of biomass for generating heat and electric energy is substantiated. The basic reasons for using organic materials as renewable energy sources are described. The examples of industrial use of energy, produced from biomass in the EU countries are given. Suitability of various types of biomass (sunflower, buckwheat and oats husk) for further thermo-chemical conversion to produce alternative fuel is experimentally investigated. When generalizing the physical and technical characteristics of different types of biomass, the results of studying a number of agricultural waste, as well as foreign authors’ data were used. The results of the technical analysis (moisture content, ash content, calorific value) of several analytical samples of agricultural waste are given. The elemental composition of some types of plant material is studied, thus allowing to state that the mentioned agricultural waste is highly reactive fuel with high volatile-matter yield. The mineral composition of organic waste: oxides of silicon (40...87 %), iron (0.2...7.7 %), calcium (0.6...30.6 %) and potassium (6.2...20 %), which has no significant effect on the heating surface contamination is investigated. The data on the elemental composition of peat, its calorific value, as well as on the products of peat decomposition at different temperatures (350, 400, 450, 520°C) are submitted. Based on the content of ash, water-insoluble substances, lignin, hemicellulose and cellulose, wood composition depending on the breed is determined.